Parent‐Reported Medication Side Effects and Their Impact on Health‐Related Quality of Life in Children With Juvenile Idiopathic Arthritis. Issue 10 (14th June 2022) - Chédeville, Gaëlle; McGuire, Katherine; Cabral, David A.; Shiff, Natalie J.; Rumsey, Dax G.; Proulx‐Gauthier, Jean‐Philippe; Schmeling, Heinrike; Berard, Roberta A.; Batthish, Michelle; Soon, Gordon; Gerhold, Kerstin; Gerschman, Tommy; et al.
Abstract : Objective: To describe the frequency and severity of parent‐reported medication side effects (SEs) in children with juvenile idiopathic arthritis (JIA) relative to physician‐reported actionable adverse events (AEs), and to assess their impact on health‐related quality of life (HRQoL). Methods: Newly diagnosed JIA patients recruited between 2017 and 2019 to the Canadian Alliance of Pediatric Rheumatology Investigators (CAPRI) Registry were included. Parents reported presence and severity (0 = no problem, 10 = very severe) of medication SEs at every clinic visit. Physicians were asked to report any actionable AE. HRQoL was assessed using the Quality of My Life (QoML) questionnaire (0 = the worst, 10 = the best) and parent's global assessment (0 = very well, 10 = very poor). Analyses included proportion of visits with SEs or actionable AEs, cumulative incidence by Kaplan‐Meier methods, and HRQoL impact measured with longitudinal mixed‐effects models. Results: SEs were reported at 371 of 884 (42%) visits (95% confidence interval [95% CI] 39, 45%) in 249 patients, with a median of 2 SEs per visit (interquartile range [IQR] 1–3), and median severity of 3 (IQR 1.5–5). Most SEs were gastrointestinal (32.5% of visits) or behavioral/psychiatric (22.4%). SE frequency was lowest with nonsteroidal antiinflammatory drugs alone (34.7%) and highest with prednisone and methotrexate combinations (66%). SE cumulative incidence was 67% (95% CI 59, 75) within 1 year of diagnosis, and 36% (95% CI 28, 44) for actionable AEs. Parent global and QoML scores were worse with SEs present; the impact persisted after adjusting for pain and number of active joints. Conclusion: Parents report that two‐thirds of children with JIA experience SEs impacting their HRQoL within 1 year of diagnosis. SE mitigation strategies are needed in managing JIA.